2021
DOI: 10.3390/antiox11010087
|View full text |Cite
|
Sign up to set email alerts
|

Allicin, an Antioxidant and Neuroprotective Agent, Ameliorates Cognitive Impairment

Abstract: Allicin (diallylthiosulfinate) is a defense molecule produced by cellular contents of garlic (Allium sativum L.). On tissue damage, the non-proteinogenic amino acid alliin (S-allylcysteine sulfoxide) is converted to allicin in an enzyme-mediated process catalysed by alliinase. Allicin is hydrophobic in nature, can efficiently cross the cellular membranes and behaves as a reactive sulfur species (RSS) inside the cells. It is physiologically active molecule with the ability to oxidise the thiol groups of glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 192 publications
(194 reference statements)
0
25
0
Order By: Relevance
“…It has also been shown that the antiangiogenic effect of garlic compounds is due to its inhibitory effect on particular signaling pathways in nondiabetic cell models, including VEGF, AKT/ERK, and NO pathways [27]. Moreover, several reports are indicating the neuroprotective and neuroregenerative effects of garlic [28][29][30][31]. Accordingly, garlic is suggested to enhance the antiangiogenic effect of intravitreal anti-VEGF agents, protect the neural retina from oxidant damages, suppress the inflammation process that is responsible for the pathogenesis of DME, and can be an effective complementary treatment in the management of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the antiangiogenic effect of garlic compounds is due to its inhibitory effect on particular signaling pathways in nondiabetic cell models, including VEGF, AKT/ERK, and NO pathways [27]. Moreover, several reports are indicating the neuroprotective and neuroregenerative effects of garlic [28][29][30][31]. Accordingly, garlic is suggested to enhance the antiangiogenic effect of intravitreal anti-VEGF agents, protect the neural retina from oxidant damages, suppress the inflammation process that is responsible for the pathogenesis of DME, and can be an effective complementary treatment in the management of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Alliinase and alliin form an enzyme-substrate complex in the presence of water, at an optimum temperature of 33 • C and pH of 6.5. Indeed, the enzyme is sensitive to acids, suggesting the employment of enteric-coated formulations of garlic supplements [11,31,32]. Allicin (the most abundant thiosulfinate formed via allinase reactions, approximately 70%) is poorly soluble in water and is responsible for a pungent and unpleasant flavor, but it is very unstable and easily transformed into a high number of products, classified as oilsoluble compounds, mainly including dithiins (formed by the dimerization of thioacrolein created via allicin β-elimination), followed by ajoene, allyl methyl trisulfide (AMTS), diallyl sulfide (DAS), diallyl disulfide (DADS), and diallyl trisulfide (DATS).…”
Section: Allicin and Organo-sulfur-containing Compounds (Oscs)mentioning
confidence: 99%
“…Recently, the healthy properties of allicin have been widely characterized in terms of neuroprotection for AD therapy [11,88]. A comparison between raw and steamed garlic has been performed in terms of anti-inflammatory activities in LPS-stimulated BV2 microglial cells.…”
Section: Allicinmentioning
confidence: 99%
See 1 more Smart Citation
“…As the brain is highly susceptible to oxidative damage, it has been suggested that inadequate antioxidant defences might mediate the pathogenesis and progression of dementia [ 61 ]. Many antioxidant nutrients such as vitamin C, vitamin E [ 62 ], zinc [ 63 ] (cofactor for enzymes with antioxidative activity) and carotenoids [ 64 ], and non-nutrient food ingredients like polyphenols [ 65 ], anthocyanins [ 66 ], lignans [ 67 ] or allicin [ 68 ] have been proven to be beneficial for age-related cognitive impairment. But, as far as there is not a deficit of the mentioned nutrients or a pathological situation, clinical trials with supplementation of these mentioned antioxidant compounds have not demonstrated a beneficial effect on any cognitive outcome in healthy patients [ 10 ].…”
Section: Bioactive Compounds and Improvement In Cognitive Functionmentioning
confidence: 99%